Challenges of higher education in Peru during the COVID-19 pandemic - Vilela Alemán, Patty (2021)
This essay describes and reflects on the experience of higher education in the context of the public health emergency generated by COVID-19 and declared in Peru from March 11, 2020 to the present. The physical locking of university settings has created great challenges for students and teachers across the country. The changes, mostly forced and unplanned, generated uncertainty and discontent in teachers and students. In this document, the authors seek to approach this experience in order to propose lessons learned and reflections on this situation that, as humanity, it is necessary to document for future generations.